THE EFFECT OF MOTIVATION AND WORK DISCIPLINE ON PERFORMANCE OF EMPLOYEES AT UPBJJ OFFICE UT MEDAN - Hernawi Silalahi; Johannes; Kula Ginting (Sensei International Journal of Education and Linguistic, 2021)
This study aims to analyze the effect of motivation and work discipline on employee performance at the UPBJJ UT Medan office. According to the research objectives, the research data were obtained from questionnaires, observations, and related literature studies. The analysis technique uses multiple linear regression with hypothesis testing, namely the F test and T-test. The number of samples is 35 respondents using the incidental sampling technique. The results showed that the variables of motivation and work discipline had a significant effect either partially or simultaneously on employee performance at the UPBJJ UT Medan office.